(3GdeYGhOI aj CeQ GdfaSs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3hUdJ GdeSFdI hGdeYGhOI ai CeQ GdfaS CWGd Gddg HbGA GdTjN GdaGVd hhbaJ GdBf Ydi ZQVg ajgG hUGOaJg dYd de jJCed eG bdJg s
(3BNQgG (B:s
(3hLhOkG ef PGJgG hdjS cd eG djS hLhOg ef PGJg jLhR Ef fRd hLhOg hgh GdPi djS ajg GdJQcjH GdePchQ hGdMeO ddg dhGgH GdYbd JeJ GdQSGdI s
(3HgG fXGe GdJYbjHIs
(3cJHgG GHf SjfG Edi JdejPg CHj YHjOI GdLhRLGfis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3eUOQ GbJfGA GdCUd (B:s
(3GdBUajI HMjOQ CHGO (B((3eLGejY (B11) s
Keywords: (3GdadSaI hGdefWbs